Internalisasi Nilai Kejujuran dalam Pendidikan Anti Korupsi bagi Mahasiswa - Amiruddin Abdullah; Nurbaiti (Scientific Journal for Nation Building, 2025)
This article discusses the internalization of the value of honesty in anti-corruption education as a strategic effort to develop students' integrity-based character. Honesty is regarded as a fundamental value that must be strongly instilled in students to combat various forms of corrupt behavior, both within the academic environment and in broader society. This research is a qualitative study using a literature review method by analyzing various relevant sources such as books, academic journals, and research reports. The findings indicate that anti-corruption education that emphasizes honesty can cultivate students who are honest, responsible, and possess strong social awareness and professional ethics. The internalization of honesty also contributes to social development and prepares students to face challenges in professional settings. Therefore, anti-corruption education at the university level must integrate the value of honesty comprehensively into both academic instruction and campus life practices.